2016
DOI: 10.3346/jkms.2016.31.9.1485
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Intraoperative Infusion of Dexmedetomidine, Fentanyl, and Remifentanil on Perioperative Hemodynamics, Sedation Quality, and Postoperative Pain Control

Abstract: We aimed to compare fentanyl, remifentanil and dexmedetomidine with respect to hemodynamic stability, postoperative pain control and achievement of sedation at the postanesthetic care unit (PACU). In this randomized double-blind study, 90 consecutive total laparoscopic hysterectomy patients scheduled for elective surgery were randomly assigned to receive fentanyl (1.0 µg/kg) over 1 minute followed by a 0.4 µg/kg/hr infusion (FK group, n = 30), or remifentanil (1.0 µg/kg) over 1 minute followed by a 0.08 µg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…35,36 Favorable postoperative pain management makes for adequate analgesia and sedation. [37][38][39] Our present study showed attenuated agitation as demonstrated by significantly reduced SAS score in the group T compared with group C, which was in line with our results of the postoperative pain score, indicating that additional intraoperative administration of sufentanil is helpful for proper postoperative pain management in patients undergoing laparoscopic myomectomy. The release of stress factors and inflammatory mediators caused by surgical or anesthetic operations may directly cause pain and affect patients' postoperative recovery.…”
Section: Discussionsupporting
confidence: 90%
“…35,36 Favorable postoperative pain management makes for adequate analgesia and sedation. [37][38][39] Our present study showed attenuated agitation as demonstrated by significantly reduced SAS score in the group T compared with group C, which was in line with our results of the postoperative pain score, indicating that additional intraoperative administration of sufentanil is helpful for proper postoperative pain management in patients undergoing laparoscopic myomectomy. The release of stress factors and inflammatory mediators caused by surgical or anesthetic operations may directly cause pain and affect patients' postoperative recovery.…”
Section: Discussionsupporting
confidence: 90%
“…). Sub‐group analyses according to the type of medication used for anaesthetic maintenance suggested a similar effect in both the volatile anaesthetic (mean difference (95%CI): 0.6 (0.0–1.1); I 2 = 87%; p = 0.05) and propofol sub‐groups (mean difference (95%CI): 1.3 (0.7, 1.8); I 2 = 85%; p < 0.0001), with no difference between sub‐groups (p = 0.05). With regard to the funnel plots for our primary outcome, the Duval and Tweedie's trim and fill test revealed the point estimates (95%CI) for the combined studies to be −0.48 (−0.64 to −0.32); using trim and fill, these values are unchanged, suggesting that no trials are missing from the meta‐analysis.…”
Section: Resultsmentioning
confidence: 92%
“…All studies included a total of patients ranging from 30 to 88, with the exception of one study that included a total of 139 patients . Nine trials included patients scheduled for laparoscopic surgery , seven for ear, nose and throat surgery , and five for different types of elective operations . Fourteen (66%) included trials used volatile anaesthetic to maintain anaesthesia and seven that administered propofol .…”
Section: Resultsmentioning
confidence: 99%
“… 70 IV DEX at sedative doses initiated at the end of main procedures of the surgery to the time in the PACU resulted in better postoperative hemodynamic stability than fentanyl or remifentanil with a similar effect of pain control in the PACU. 71 DEX as an intrathecal adjuvant with ropivacaine for spinal anesthesia provided better postoperative analgesia after infraumbilical surgeries as compared with MgSO 4 . 72 DEX as an epidural adjuvant had a greater analgesic and local anesthetic-sparing effect, compared with fentanyl, in the early postoperative period in children undergoing major orthopedic lower extremity surgery.…”
Section: Pharmacological Managementmentioning
confidence: 98%